Promoting Resilience in Adolescents from Divorced Family: The Role of Social Support and Self-Efficacy - Murniasih, Farhanah; Irvan, Moh (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
Divorce can be a tumultuous experience for adolescents; social support and self-efficacy are recognized as crucial factors in helping them navigate the challenges. Resilience, which pertains to an individual's ability to adapt positively to adversity, is essential during this transitional period. This research delves into the evolving understanding of how social support impacts resilience in adolescents from divorced families, with self-efficacy as a mediator. The research involved 400 respondents (318 females and 82 males) aged 15-21 from divorced families. Data were collected using the Resilience Scale (12 items, ), General Self Efficacy Scale (10 items, , and Social Provisions Scale (26 items, . The data analysis techniques applied in this study were descriptive, correlational, and regression-based mediating analyses. The mediating analysis used the PROCESS syntax in IBM SPSS. This study showed that social support increased resilience in adolescents from divorced families, and self-efficacy mediates social support and resilience. This study confirmed that self-efficacy partially mediates social support and resilience in adolescents from divorced families.